The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/jmv.26082
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the variables collected at admission and progression to severe cases during hospitalization among patients with COVID‐19 in Chongqing

Abstract: Funding information Chongqing Science and Technology Bureau "new crown pneumonia epidemic emergency science and technology special" the fourth batch of projects; Chongqing Education Board "new coronavirus infection and prevention" emergency scientific research project

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 16 publications
5
58
1
Order By: Relevance
“…Overall, 84 studies were included in the final analyses. Of them, 60 studies reported on a total of 5487 subjects with severe COVID-19 and 9670 subjects with mild COVID-19 [ 6 , 8 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, 84 studies were included in the final analyses. Of them, 60 studies reported on a total of 5487 subjects with severe COVID-19 and 9670 subjects with mild COVID-19 [ 6 , 8 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ,…”
Section: Resultsmentioning
confidence: 99%
“…The heterogeneity among studies was significant (I 2 : 84.3%, p < 0.001) and was not reduced by the exclusion of one study at a time. In contrast, no difference was found in 23 studies [6,8,25,26,31,32,35,36,38,40,41,[44][45][46]51,54,63,64,67,68,73,76,81] reporting aPTT values between 1018 subjects with severe COVID-19 In contrast, no difference was found in 23 studies [6,8,25,26,31,32,35,36,38,40,41,[44][45][46]51,54,63,64,67,68,73,76,81] reporting aPTT values between 1018 subjects with severe COVID-19 and 3976 subjects with mild disease (SMD: 0.04; 95%CI: −0.17, 0.25, p = 0.701; I 2 : 86.1%, p < 0.001, Figure 2). and 3976 subjects with mild disease (SMD: 0.04...…”
Section: Study Group 1 (Severe Covid-19 Vs Mild Covid-19)mentioning
confidence: 86%
See 2 more Smart Citations
“…Covid-19 severity levels can be categorized as mild, moderate, severe, and critical conditions ( Figure 1 ) [ 28 , 29 ]. Mild disease is defined as patients without dyspnea, without clinical evidence of respiratory distress, no pneumonia on imaging, and blood oxygen saturation maintained above 93% under resting conditions [ 30 , 31 ]. Fever (<39.1 °C) and cough are seen frequently, even in mild disease.…”
Section: Criteria For Determining Severitymentioning
confidence: 99%